Preparation of neuron-inspired CNT (at) DU composite material and application of neuron-inspired CNT (at) DU composite material in carbon capture

By using neuron-inspired CNT@DU composites in the mixed matrix membrane, an interactive transmission network was constructed, which solved the problem of removing high carbon dioxide in natural gas, and achieved efficient CO2 capture and increased natural gas calorific value.

CN119656883APending Publication Date: 2025-03-21SHIHEZI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411846674.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove high content of carbon dioxide in natural gas, resulting in pipeline corrosion and reduced natural gas calorific value.

Method used

Using neuron-inspired CNT@DU composite material as filler, an interactive transmission network is constructed in a mixed matrix membrane to improve gas separation performance and be used for carbon capture.

Benefits of technology

The efficient separation of CO2/CH4 mixed gas was achieved, with the maximum CO2 flux of 851.3±17Barrer and the CO2/CH4 selectivity was 25.9±0.3, which significantly improved the capture efficiency of carbon dioxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005189389500000011
    Figure HDA0005189389500000011
  • Figure HDA0005189389500000012
    Figure HDA0005189389500000012
  • Figure HDA0005189389500000021
    Figure HDA0005189389500000021
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of mixed matrix membrane materials, in particular to preparation of a neuron-inspired CNT (at) DU composite material and application of the neuron-inspired CNT (at) DU composite material in carbon capture. The invention provides a preparation method of a neuron inspired CNT (at) DU composite material. The prepared CNT (at) DU is taken as a filling agent and is physically blended with auto-polymerization constrained Pebax / PEG-MEA (SPM) to form a mixed matrix membrane. The SPM / CNT (at) DU mixed matrix membrane prepared by the method has the advantages of simple preparation process, controllable reaction, cheap and easily available raw materials and mild conditions, and can powerfully promote advantage complementation of a metal organic framework and a polymer matrix. Under the inspiration of a neuron structure, the CNT (at) DU is composed of DUiO-66 which simulates a cell body and CNT which simulates a synapse, so that the CNT (at) DU can play a role of an interactive neuron inspiration transmission network. Wherein the "synaptic imitation" CNTs provide a long distance and ordered channel for rapid CO2 transfer between adjacent DUiO-66. In addition, due to the fact that DUiO-66 of a cell body-like body has an unsaturated active Zr < 4 + > site, CO2 can be rapidly captured. The prepared mixed matrix membrane has an interactive neuron inspiration transfer network, and can strengthen the transfer of CO2 in the membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of mixed matrix membrane material preparation, and in particular to the preparation of a neuron-inspired CNT@DU composite material and its application in carbon capture. Background Art

[0002] CCUS (Carbon Capture Utilization Storage) is one of the key technologies to address global climate change and has received widespread attention from the whole society. Therefore, reducing emissions and lowering the concentration of carbon dioxide in the atmosphere are urgent tasks that need to be given high attention. Since fossil fuels will remain the main source of energy for the foreseeable future, the most direct strategy to reduce anthropogenic carbon dioxide emissions is to eliminate carbon dioxide at the source. Therefore, in order to alleviate the sharply increasing global energy demand and environmental problems, the requirements for sustainable energy storage technology are high.

[0003] Natural gas (NG) can provide higher calorific value and lower carbon dioxide emissions compared to other hydrocarbon fuels such as coal and oil. About 30% of the energy currently consumed worldwide is produced by natural gas, and in addition, a large part of natural gas is transported around the world in liquid form. Natural gas (NG) has become one of the most useful, cleanest and cheapest energy sources in the world. It is estimated that global natural gas consumption will increase at an average annual rate of 2.3% from 2002 to 2025. It is estimated that one-third of the proven natural gas reserves are acidic. In its raw form, it mainly consists of methane (CH4), varying amounts of heavier gaseous hydrocarbons, acid gases, water vapor, mercury, radioactive gases and other gases. The CO2 content in natural gas is about 20%, and NG needs further purification. Optimal separation of carbon dioxide from natural gas is necessary because it reduces the calorific value of natural gas combustion and affects the selling price of natural gas. The high carbon dioxide content in natural gas promotes the formation of carbonic acid and dry ice, and even worse, it can cause pipeline corrosion and increase the volume of gas transported by pipelines. CO2 concentrations above 2% or 3% significantly reduce the BTU value (heat capacity) of the gas, making it economically unviable. Therefore, from an industrial perspective, in the natural gas industry (NG) for specific liquefied natural gas processing (LNG), industry standards require CO2 concentrations below 50ppm to address issues such as pipeline corrosion and reduced calorific value of natural gas due to the presence of CO2, so removing CO2 from natural gas through purification processes is essential to improving product quality. A prerequisite for achieving this goal is the adoption of low-cost, energy-efficient carbon capture and storage technology. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a preparation of a neuron-inspired CNT@DU composite material and its application in carbon capture. The neuron-inspired CNT@DU composite material prepared by the present invention is used as a filler to construct an interactive transmission network in a mixed matrix membrane to improve gas separation performance for carbon capture.

[0005] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:

[0006] In a specific embodiment, the present invention provides a method for preparing a neuron-inspired CNT@DU composite material, the method comprising the steps of:

[0007] (1) The carbon nanotubes are fully dispersed in a concentrated nitric acid solution, heated under reflux and stirred. The obtained acidified product is repeatedly washed and filtered with water until the pH value of the filtrate is about 7. It is then dispersed in a prepared NaOH solution and the pH is adjusted to about 10. It is then further dried in a vacuum oven to obtain carboxylated carbon nanotubes.

[0008] (2) Dissolving ZrCl4 in N,N-dimethylformamide (DMF), then slowly adding the carboxylated carbon nanotubes synthesized in step (1) into the above solution, and performing ultrasonic reaction at room temperature to obtain a precursor solution.

[0009] (3) Based on the precursor solution prepared in step (2), H2BDC, benzoic acid and the precursor solution are evenly mixed, continuously stirred at a certain temperature, and centrifuged after the reaction is completed, and washed with DMF and an appropriate amount of methanol. Finally, it is dried in a vacuum oven and thermally activated in a box-type high-temperature muffle furnace to obtain CNT@DU.

[0010] Furthermore, in step (1), the amount of the carbon nanotubes and concentrated nitric acid is in the ratio of 2 g to 50 mL; the stirring temperature is 70 to 90° C., and the stirring time is 36 to 48 hours.

[0011] The amount of ZrCl4, carboxylated carbon nanotubes and DMF used in step (2) is 0.6 g: 0.36 g: 120 mL.

[0012] In step (3), the amount of H2BDC and benzoic acid used is 0.4g:8.8g; the stirring temperature is 100-120°C, and the stirring time is 20h-24h.

[0013] In a specific embodiment, the present invention also provides a neuron-inspired CNT@DU composite material prepared by the above preparation method.

[0014] In a specific embodiment, the present invention also provides the application of the above-mentioned neuron-inspired CNT@DU composite material in carbon capture.

[0015] In a specific embodiment, the present invention also provides a mixed matrix membrane, wherein the mixed matrix membrane uses a neuron-inspired CNT@DU composite material as a filler and a self-polymerized constrained Pebax / PEG-MEA (SPM) as a base material, and the filler and the base material are physically blended at room temperature to form the mixed matrix membrane; the thickness of the mixed matrix membrane is 169 to 186 μm; the mass percentage of the filler in the mixed matrix membrane is 1% to 7%.

[0016] Furthermore, the present invention also provides the use of the mixed matrix membrane in CO2 capture.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention provides a method for preparing a neuron-inspired CNT@DU composite material, and uses the prepared CNT@DU as a filler and physically blends it with an SPM matrix to form a mixed matrix membrane. The SPM / CNT@DU mixed matrix membrane prepared by the method of the present invention has a simple preparation process, controllable reaction, and cheap and readily available raw materials. Inspired by the structure of neurons, CNT@DU is composed of "cell body-mimicking" DUiO-66 and "synapse-mimicking" CNTs, so CNT@DU can play the role of an interactive "neuron-inspired" transmission network. Among them, the "synapse-mimicking" CNT provides a long-distance and orderly channel for rapid CO2 transfer between adjacent DUiO-66. In addition, since the "cell body-mimicking" DUiO-66 has unsaturated active Zr 4+ sites, which can quickly capture CO2. The prepared mixed matrix membrane has an interactive "neuron-inspired" transmission network that can enhance the transmission of CO2 in the membrane.

[0019] The present invention combines the advantages of CNT and DUiO-66 fillers to achieve synergistic effects; the preparation process of the mixed matrix membrane is simple, the reaction is controllable, the raw materials are cheap and readily available, and the conditions are mild, which can promote the complementary advantages of inorganic fillers and polymer matrices. The research results show that the permeation selectivity of the present invention for CO2 / CH4 mixed gas has a maximum CO2 flux of 851.3±17 Barrer and a CO2 / CH4 selectivity of 25.9±0.3. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0021] Figure 1This is a transmission electron microscope image of the CNT@DU material prepared in Example 1.

[0022] Figure 2 This is a scanning electron microscope cross-sectional image of the SPM / CNT@DU(1) mixed matrix membrane prepared in Example 1.

[0023] Figure 3 This is a scanning electron microscope cross-sectional image of the SPM / CNT@DU(3) mixed matrix membrane prepared in Example 2.

[0024] Figure 4 This is a scanning electron microscope cross-sectional image of the SPM / CNT@DU(5) mixed matrix membrane prepared in Example 3.

[0025] Figure 5 This is a scanning electron microscope cross-sectional image of the SPM / CNT@DU(7) mixed matrix membrane prepared in Example 4.

[0026] Figure 6 This is a scanning electron microscope cross-sectional image of the SPM film prepared in Comparative Example 1.

[0027] Figure 7 This is a scanning electron microscope cross-sectional image of the SPM / DUiO-66(5) mixed matrix membrane prepared in Comparative Example 2. DETAILED DESCRIPTION

[0028] The present invention will be further explained below. These examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Experimental methods without specific conditions in the examples are all based on conventional conditions. The reagents and materials used, unless otherwise specified, can be obtained from commercial channels.

[0029] Embodiment 1:

[0030] A SPM / CNT@DU (1) mixed matrix membrane was prepared. The thickness of the mixed matrix membrane was 173 μm. The mixed matrix membrane used SPM as a membrane matrix and CNT@DU was added to the membrane matrix. The mass ratio of SPM to CNT@DU was 0.99:0.01. The preparation method of the mixed matrix membrane was as follows:

[0031] Step 1: Preparation of CNT@DU:

[0032] 2g carbon nanotubes were fully dispersed in 50mL concentrated nitric acid solution, heated to reflux at 80℃ and stirred for 48h. The obtained acidified product was repeatedly washed and filtered with water until the pH value of the filtrate was about 7. It was then dispersed in the prepared NaOH solution and the pH was adjusted to about 10. It was then further dried in a vacuum oven to obtain carboxylated carbon nanotubes. 0.6g ZrCl4 was dissolved in 120mL DMF solution, and then 0.36g carboxylated carbon nanotubes were slowly added to the above solution, and ultrasonic reaction was performed at room temperature to obtain a precursor solution. 0.4g H2BDC and 8.8g benzoic acid were mixed evenly with the precursor solution, stirred continuously at 120℃ for 24h, and centrifuged after the reaction was completed, and washed with DMF and an appropriate amount of methanol. Finally, it was dried in a vacuum oven and thermally activated in a box-type high-temperature muffle furnace to obtain CNT@DU.

[0033] Please refer to Figure 1 As shown in the figure, the elongated CNTs are not only embedded in the DUiO-66 particles, but also form a network as a connection between the particles. Based on the principle of electrostatic attraction, it is believed that the Zr in ZrCl4 4+ It is easily attracted by the negative oxygen functional groups in CNTs and adsorbed on the CNT surface. In this way, DUiO-66 seed crystals can be concentrated on the CNT surface for nucleation, and DUiO-66 particles are interwoven by CNTs to form an interconnected network. The interactive transfer network promotes the construction of fast CO2 transmission channels in MMMs. This interactive "neuron-inspired" transfer network can enhance the transfer of CO2 in the membrane.

[0034] Step 2: Preparation of SPM solution:

[0035] Weigh 0.537g of 1657 particles and 0.358 g of PEG-MEA were dissolved in 10 mL of a mixed solution of ethanol and water (the mass ratio of ethanol to water was 70% / 30%), heated in a water bath at 80°C with stirring for 2 h to completely dissolve Pebax and PEG-MEA, and then added with 1 wt.% AIBN to room temperature to prepare a 6 wt.% SPM matrix solution for later use.

[0036] Step 3: Preparation of SPM / CNT@DU mixed matrix membrane:

[0037] The CNT@DU (0.009 g) prepared in step 1 was physically blended with the 6 wt.% SPM solution prepared in step 2, and stirred at room temperature for 4 h to obtain a casting solution, which was then poured onto a clean culture dish for casting. The mixture was dried at room temperature (25°C) for 48 h, and then vacuum dried at 40°C in a vacuum drying oven to remove the residual solvent on the surface of the mixed matrix membrane, and then thermally initiated at 80°C to fully polymerize the mixture to obtain a SPM / CNT@DU mixed matrix membrane with a thickness of 173 μm. The weight percentage of CNT@DU in the SPM / CNT@DU mixed matrix membrane was 1%, so it was named SPM / CNT@DU (1) mixed matrix membrane.

[0038] Please refer to Figure 2 As shown: Under the conditions of 25℃ and 2bar, the SPM / CNT@DU(1) mixed matrix membrane was used for the separation test of CO2 / CH4 mixed gas with a CO2 volume fraction of 20%. Its CO2 flux was 636.9±6Barrer and the CO2 / CH4 selectivity was 20.5±0.3.

[0039] Embodiment 2:

[0040] A SPM / CNT@DU(3) mixed matrix membrane was prepared. The difference from the SPM / CNT@DU(1) mixed matrix membrane in Example 1 is that the thickness of the obtained SPM / CNT@DU(3) mixed matrix membrane is 176 μm, wherein the mass ratio of SPM to CNT@DU is 0.97:0.03. The preparation method of the mixed matrix membrane is different from that of Example 1 only in that in step 3, 0.027 g of CNT@DU is weighed instead of 0.009 g CNT@DU; finally, a mixed matrix membrane with a thickness of 176 μm is obtained.

[0041] Please refer to Figure 3 As shown: Under the conditions of 25°C and 2 bar, the SPM / CNT@DU(3) mixed matrix membrane prepared in Example 2 was used for the separation test of CO2 / CH4 mixed gas with a CO2 volume fraction of 20%, and its CO2 flux was 729.1±3 Barrer and CO2 / CH4 selectivity was 22.8±0.2.

[0042] Embodiment 3:

[0043] A SPM / CNT@DU(5) mixed matrix membrane was prepared. The difference from the SPM / CNT@DU(1) mixed matrix membrane in Example 1 is that the thickness of the obtained SPM / CNT@DU(5) mixed matrix membrane is 180 μm, wherein the mass ratio of SPM to CNT@DU is 0.95:0.05. The preparation method of the mixed matrix membrane is different from that of Example 1 only in that in step 3, 0.045 g CNT@DU is weighed instead of 0.009 g CNT@DU; finally, a mixed matrix membrane with a thickness of 180 μm is obtained.

[0044] Please refer to Figure 4 As shown: Under the conditions of 25°C and 2 bar, the SPM / CNT@DU(5) mixed matrix membrane prepared in Example 3 was used for the separation test of CO2 / CH4 mixed gas with a CO2 volume fraction of 20%, and its CO2 flux was 851.3±17 Barrer and CO2 / CH4 selectivity was 25.9±0.3.

[0045] Embodiment 4:

[0046] A SPM / CNT@DU(7) mixed matrix membrane was prepared. The difference from the SPM / CNT@DU(1) mixed matrix membrane in Example 1 is that the thickness of the obtained SPM / CNT@DU(7) mixed matrix membrane is 186 μm, wherein the mass ratio of SPM to CNT@DU is 0.93:0.07. The preparation method of the mixed matrix membrane is different from that of Example 1 only in that in step 3, 0.009 g of CNT@DU is weighed instead of 0.063 g of CNT@DU; finally, a mixed matrix membrane with a thickness of 186 μm is obtained.

[0047] Please refer to Figure 5 As shown: Under the conditions of 25°C and 2 bar, the SPM / CNT@DU(7) mixed matrix membrane prepared in Example 4 was used for the separation test of CO2 / CH4 mixed gas with a CO2 volume fraction of 20%, and its CO2 flux was 760.8±9 Barrer and CO2 / CH4 selectivity was 23.2±0.2.

[0048] Comparative Example 1

[0049] Prepare an SPM film with a thickness of 169 μm. The preparation method is as follows: weigh 0.537 g of 1657 particles and 0.358g of PEG-MEA were dissolved in 10mL of ethanol and water mixed solution (the mass ratio of ethanol to water was 70% / 30%), heated in a water bath at 80°C for 2h with stirring to completely dissolve the Pebax particles and PEG-MEA, and added 1wt.% of AIBN to room temperature to obtain a 6wt.% SPM casting solution. The casting solution was poured on a clean culture dish and cast, dried at room temperature (25°C) for 48h, and then the residual solvent on the surface of the mixed matrix membrane was removed in a vacuum drying oven at 40°C, and then thermally initiated at 80°C to fully polymerize to obtain a self-polymerized constrained SPM membrane with a membrane thickness of 169μm.

[0050] Please refer to Figure 6 As shown: Under the conditions of 25°C and 2 bar, the SPM membrane prepared in the comparative example was used for the separation test of CO2 / CH4 mixed gas with a CO2 volume fraction of 20%, and its CO2 flux was 410.2±10 Barrer and CO2 / CH4 selectivity was 15.2±0.4.

[0051] Comparative Example 2

[0052] The SPM / DUiO-66(5) mixed matrix membrane was prepared. The difference from the SPM / DUiO-66(5) mixed matrix membrane in Example 3 was that in step 3, 0.045 g of CNT@DU was replaced by 0.045 g of DUiO-66. Finally, a mixed matrix membrane with a thickness of 175 μm was obtained.

[0053] Please refer to Figure 7 As shown: Under the conditions of 25°C and 2 bar, the SPM / DUiO-66(5) mixed matrix membrane prepared in Comparative Example 2 was used for the separation test of CO2 / CH4 mixed gas with a CO2 volume fraction of 20%, and its CO2 flux was 675.2±8 Barrer and CO2 / CH4 selectivity was 23.2±0.5.

[0054] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a neuron-inspired CNT@DU composite material, characterized in that: The preparation method comprises the following steps: (1) The carbon nanotubes are fully dispersed in a concentrated nitric acid solution, heated under reflux and stirred. The obtained acidified product is repeatedly washed and filtered with water until the pH value of the filtrate is about 7. It is then dispersed in a prepared NaOH solution and the pH is adjusted to about 10. It is then further dried in a vacuum oven to obtain carboxylated carbon nanotubes. (2) Dissolve ZrCl4 in N,N-dimethylformamide (DMF), then slowly add the carboxylated carbon nanotubes treated in step (1) into the above solution, and perform ultrasonic reaction at room temperature to obtain a precursor solution. (3) Based on the precursor solution prepared in step (2), H2BDC, benzoic acid and the precursor solution are evenly mixed, continuously stirred at a certain temperature, and centrifuged after the reaction is completed, and washed with DMF and an appropriate amount of methanol. Finally, it is dried in a vacuum oven and thermally activated in a box-type high-temperature muffle furnace to obtain CNT@DU.

2. The preparation method according to claim 1, characterized in that: (1) In step (1), the amount of carbon nanotubes and concentrated nitric acid used is 2 g:50 mL; the stirring temperature is 70-90° C., and the stirring time is 36 h to 48 h. (2) The amount of ZrCl4, carboxylated carbon nanotubes and DMF used in step (2) is 0.6 g: 0.36 g: 120 mL. (3) In step (3), the amount of H2BDC and benzoic acid used is 0.4 g:8.8 g; the stirring temperature is 100-120°C, and the stirring time is 20 h to 24 h.

3. Application of the neuron-inspired CNT@DU composite material according to claim 1 in carbon capture.

4. A mixed matrix membrane, wherein the mixed matrix membrane uses a neuron-inspired CNT@DU composite material as a filler and a self-polymerized constrained Pebax / PEG-MEA (SPM) as a base material, and the filler and the base material are physically blended at room temperature; the thickness of the mixed matrix membrane is 169 to 186 μm; the mass percentage of the filler in the mixed matrix membrane is 1% to 7%.

5. Use of the mixed matrix membrane according to claim 4 in CO2 capture.